Real-time modulation of perceptual eye dominance in humans - Zhou, Jiawei (The Royal Society, 2014)
Ocular dominance (OD) has long served as the model for neural plasticity. The shift of OD has been demonstrated by monocular deprivation in animals only during early visual development. Here, for the first time, we show that perceptual eye dominance can be modulated in real time in normal human adults by varying the spatial image content of movies seen dichoptically by the two eyes over a period as short as 2.5 h. Unlike OD shifts seen in early visual development, this modulation in human eye dominance is not simply a consequence of reduced interocular correlation (e.g. synchronicity) or overall contrast energy, but due to the amplitude reductions of specific image components in one eye's view. The spatial properties driving this eye dominance change suggest that the underlying mechanism is binocular but not orientationally selective, therefore uniquely locating it to layer 4 B of area V1.